ITIJAHAT KAUN AL-NABI WA AL-RASUL FI SYAKHSIYAH MUHAMMAD FI NATSR MAULID AL-BARZANJI - Istomah, Himmah; Zuhdy, Halimi (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
One of human personalities is humanist. Based on the understanding of Maslow's theory of motivation, researcher seeks to uncover kinds of motivational needs of Muhammad Saw contained in Maulid Al-Barzanjiy (the work of Ja 'far bin Hasan al-Barzanji (d. 1763 M)). The goal is realized through a descriptive qualitative approach with text analysis about Psycholiterature of Endraswara. The results of this study indicate that in Maulid Al-Barzanji there are Muhammad Saw's five needs and how their satisfying perfectly, namely: physiological needs, safety, social, esteem, and self-actualization. Thus, it can be interpreted that Muhammad SAW as an ordinary human having motivational needs. His prophetic and apostleship honor is not a direct blessing from Allah, but he had been through some complicated processes in life. This can be applied by his followers, so they can complete their motivational needs to reach the satiation as a caliph and to be useful person in this world.